Accurate quantification of toxic elements in medicine food homologous plants using ICP-MS/MS. (15th April 2018) - Fu, Liang; Shi, Shu-Yun; Chen, Xiao-Qing
Highlights: A novel method for determination of As, Cd, Hg, and Pb in MFH plants was provided. Interferences were eliminated by oxygen shift reaction. Analytes in solution were stable after one week. The limit of detection of the method achieved ng g −1 level. The content of As and Pb in some MFH plants severely exceeded the standard. Abstract: An analytical method to accurately determine the presence of four toxic elements (As, Cd, Hg, and Pb) in medicine food homologous (MFH) plants using inductively coupled plasma-tandem mass spectrometry (ICP-MS/MS) was established. Fifty common MFH plants from different regions of China were analyzed and the range of values of As, Cd, Hg, and Pb were determined to be 66.3–2978.6 ng g −1, 13.5–8107.1 ng g −1, 1.7–325.6 ng g −1, and 61.4–11428.5 ng g −1, respectively. According to the standards of Chinese Pharmacopoeia (CP) 2010, the excess standard rates of As, Cd, Hg, and Pb were 14%, 16%, 6%, and 18%, respectively. On the basis of the limits set by the Chinese National Standards (CNS) GB 2762-2012, the excess standard rates of As, Cd, Hg, and Pb were 44%, 20%, 12%, and 34%, respectively. Therefore, special attention should be paid to the potential risk posed by toxic element contamination in MFH plants.